A Medical Writing Curriculum for Internal Medicine Residents: Using Adult Learning Theory to Teach Formal Medical Writing and Publication of Case Reports - Kristi Moore (Association of American Medical Colleges, 2015)
Abstract Introduction This curriculum is designed to provide a background in medical writing techniques and formal instruction in writing a medical case report. Although originally designed for a resident physician audience, it may also be appropriate for medical students, nurses, nursing students, and other health care professionals. Methods The curriculum is delivered in two or more live sessions with an additional at-home learning module. Part one focuses on the importance of medical writing skills, reviews formal case report formatting, and teaches a structured approach to writing a medical case report. Part two provides instruction in recognizing and remedying common errors and omissions in formal medical writing and utilizes an interactive computerized quiz to reinforce these tips. Part three discusses editing and proofreading, the use of checklists during the editing process, and HIPAA and patient privacy laws as they pertain to publication. An interactive tool is also provided, which allows learners to select the most appropriate journal for their submission based on case specialty, cost, and journal impact factor. Results Based on learner pre− and postsurvey results, the curriculum was successful in improving overall confidence and comfort level in writing a case report. At the end of the curriculum, 93% of respondents either agreed or strongly agreed that they were overall comfortable writing an abstract or medical case report as compared to only 37% in the pre-intervention survey. In addition, each resident who participated did successfully select a case and complete a written draft of a case report. Discussion It is anticipated that the majority of the case reports will be submitted for publication, either for an abstract poster presentation or for a journal publication, although the final data assessing this area will not be collected until June of 2015.